Influence System Online Tracking And Delivery Timeliness Regarding the Decision to Use J&T Express Expedition Services, Cilincing Branch , North Jakarta - Sari, Damara Kartika; Hidayat, Yusup Rachmat (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
The background of this study is based on the increasing number of e-commerce users, which has led to high demand for fast, accurate, and. real-time trackable delivery services. However, there are still customer complaints regarding the accuracy of tracking information and delivery delays, which affect customer decisions. The purpose of this study is to determine the influence of the Online Tracking System and Delivery Timeliness on Service Usage Decisions at the J&T Express Branch in Cilincing. North Jakarta. This study used a quantitative method with al descriptive approach. The population consists of J&T Express customers at the Cilincing Branch in North Jakarta. The sample in this study consisted of 100 respondents using purposive sampling. Data analysis used multiple linear regression models, T-tests, F-tests, and coefficient of determination (R) tests. The results of this study indicated that both partially and simultaneously, the variables of the Online Tracking System and Delivery Timeliness significantly influence Service Usage Decisions. This is evidenced by the F-test results, which have a significance value of 0.0000.05, The T-test results for the Online Tracking System variable are 0.000, and for the Delivery Timeliness variable are 0.005, where the value is less than 0.05. Based on the t-test results, it can be concluded that all variables, namely the Online Tracking System and Delivery Timeliness, influence the Decision to Use Services. The coefficient of determination (R) for the decision to services at J&T Express is influenced by the Online Tracking System and Delivery Timeliness variables by 0.778 or (77.8), while the remaining 22.2% is influenced by other variables outside the scope of this study. Keywords : Online Tracking, Delivery Timeliness, Service Usage Decision